RHoMIS (a standardized, cost-effective rural household survey tool) is adopted by 13 organisations to guide investments and generate information on 30,000 households in 31 countries - CGIAR Research Program on Livestock (2019)
The Rural Household Multi Indicator Survey (RHoMIS) is a standardized and flexible household survey tool developed by the International Livestock Research Institute (ILRI) and partners. It has been used by 13 research and development organizations such as IFAD, FAO, One Acre Fund, TreeAID, Global Diversity Foundation and others in 31 countries, pooling data from about 30,000 households. The tool allows standardization of data from many projects, building up a coherent, large dataset permitting cross-site analyses.